Preventive and curative effects of native yeasts on different Botrytis cinerea strains in “Superior Seedless” (Vitis vinifera L.) table grape cultured in Argentina - Flores, Cintia Belén; Pedrozo, Lina Paula; Pesce, Virginia Mercedes; Vazquez, Fabio; Nally, María Cristina (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2025)
The fermenting grape must is a dynamic, stressful, and selective habitat where many yeast species compete. Specific yeasts isolated from this habitat can play a fundamental role in table grape biocontrol of fungal diseases. The present study evaluated 225 grapevine yeasts against four Botrytis cinerea strains isolated from “Superior Seedless” grapes, considering the possible antifungal action mechanisms. Eighteen enological yeasts (13 Saccharomyces and 5 non- Saccharomyces) showed preventive antifungal activity against the four native B. cinerea strains, with disease severity varying between 0 and 49.91%. These 18 strains also presented curative activity against at least one of the B. cinerea strains assayed (severity values between 0 and 45.99%). Considering action mechanisms, thirteen yeast strains inhibited mycelial growth of at least one B. cinerea strain during dual plating (antibiosis), “killer” activity, and volatile antifungal assays. Our results showed that 7 yeast strains affected conidial germination (CG) and germinal tube length (GTL) of at least one B. cinerea isolate. Two yeast strains occupied the same niche as 4 B. cinerea strains (NOI values > 0.90). All yeast strains exhibited at least two inhibitory action mechanisms against gray rot, except for BSc140 with one mechanism. The possibility of more than one mechanism per yeast strain makes biocontrol an effective tool to prevent and cure gray rot in table grapes. Highlights: We evaluated 225 native grapevine yeasts against four Botrytis cinereastrains isolated from “Superior Seedless” grapes, considering the possible antifungal action mechanisms. Saccharomyces (13) and 5 non- Saccharomyces(5) strains showed preventive antifungal activity against native cinerea strains (4). Some grapevine yeasts (10 Saccharomycesy 4 non- Saccharomyces) presented curative activity against cinerea strains. Grapevine yeasts, with preventive and curative activity, presented different antifungal mechanisms against cinerea.